On Asymmetric Migration Patterns from Developing Countries - Rajat Acharyya; Saibal Kar (Global Labor Organization (GLO), 2017)
This paper shows that trade and emigration of skilled workers from a poor country is complementary but that between trade and emigration of unskilled workers is a substitute. The asymmetric effect of more openness to trade on the local wages seems to be crucial in driving such results. The asymmetric changes in skilled and unskilled wages generate counterintuitive outcomes regardless of the policy shock that triggers such wage effect. One of the more compelling outcomes is rise in wage inequality as influenced by asymmetric emigration patterns.
Keywords: F22; J64; O15; 330; Trade; emigration; skilled labour; specific factor; remittances; tax